2009
DOI: 10.1504/ijhvs.2009.027135
|View full text |Cite
|
Sign up to set email alerts
|

A regularised solution to the bridge weigh-in-motion equations

Abstract: Publication information Abstract:The traditional approach to Bridge Weigh-in-Motion (WIM) developed by Moses, gives good accuracy for estimating gross vehicle weights but is less accurate for individual axle weights. In this paper, Tikhonov regularisation is applied to the original Moses' equations to reduce some of the inaccuracies inherent within the algorithm. The optimal regularisation parameter is calculated using the L-curve criterion. The new regularised solution is numerically tested using simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…An additional penalty term multiplied by a regularization parameter is added into the original minimization formulation to improve the condition of the original system. The regularization technique was reported to significantly improve the accuracy of the identified axle weights; however, as the vehicle dynamics becomes more noticeable, the convergence of the regularized solution becomes slower (O'Brien et al, 2009).…”
Section: Moses' Algorithmmentioning
confidence: 99%
“…An additional penalty term multiplied by a regularization parameter is added into the original minimization formulation to improve the condition of the original system. The regularization technique was reported to significantly improve the accuracy of the identified axle weights; however, as the vehicle dynamics becomes more noticeable, the convergence of the regularized solution becomes slower (O'Brien et al, 2009).…”
Section: Moses' Algorithmmentioning
confidence: 99%
“…In recent years there have been extensive developments in the area of BWIM, as documented in the literature (Lydon et al, 2015;Richardson et al, 2014). In the most sophisticated algorithms, the static equations of Moses (1979) have been replaced by a system of differential equations of motion in an approach known as moving force identification (González et al, 2008;Law and Fang, 2001;Law et al, 1999;OBrien et al, 2009;Rowley et al, 2009). The most recent moving force identification research is reported by Zhu et al (2013) and Corbaly et al (2014).…”
Section: Review Of Previous Weigh-in-motion Systemsmentioning
confidence: 99%
“…Therefore, it can provide a solution for the long-term monitoring of our infrastructure. The B-WIM theory has been extended under a number of research initiatives [3][4][5][6], and more recently the ''BridgeMon'' project which finished in 2014 [7]. More recently, B-WIM systems have been used in conjunction with machine learning techniques to develop damage detection methods for railway bridges [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [5] has developed theoretical models for B-WIM and demonstrated that Tikhonov Regularization can be used to improve ill-conditioned Moses equations which occur when axles are closely spaced relative to the bridge span. More recently, moving force identification (MFI) techniques have been applied to measured signals to improve the accuracy of the measured axle weights [6,9,10]. These techniques have been found to improve the accuracy of the systems [5].…”
Section: Introductionmentioning
confidence: 99%